An outbreak of extensively drug-resistant and hypervirulent Klebsiella pneumoniae in an intensive care unit of a teaching hospital in Southwest China - Liu, Siyi; Ding, Yinhuan; Xu, Yifei; Li, Zhaoyinqian; Zeng, Zhangrui; Liu, Jinbo (Frontiers in Cellular and Infection Microbiology, 2022)
Extensively drug-resistant and hypervirulent Klebsiella pneumoniae (XDR-hvKp) is a new problem for patients in Intensive Care Unit (ICU) and can become an even more severe threat if resistant to tigecycline, considered one of the ‘last lines of defense’ drugs. This study collected seven non-replicated tigecycline-resistant XDR-hvKp from seven patients and performed genome analysis and epidemiological investigation using whole genome equencing (WGS) and other methods. All strains in this study were identified as ST11-KL64 and showed high resistance to antibiotics such as β-lactams, aminoglycosides, quinolones, and tigecycline, and one strain was also resistant to colistin. All strains were determined to be hvKp by the results of serum resistance assay and Galleria mellonella infection models. All strains had resistance genes blaCTX-M-65,blaKPC-2,blaLAP-2,blaTEM-1B, rmtB, and qnrS1 and virulence factors such as rmpA, rmpA2, and aerobactin (iucABCD, iutA). The expression of the AcrAB-TolC efflux pump was upregulated in all strains, and the expression levels of the gene pmrK was significantly upregulated in colistin-resistant strain DP compared to colistin-sensitive strain WT in this study. In conclusion, we described an outbreak caused by tigecycline-resistant XDR-hvKp in the ICU of a teaching hospital in southwest China. The spread of these superbugs poses a great threat to patients and therefore requires us to closely monitor these XDR-hvKp and develop relevant strategies to combat them.